Pengaruh penambahan susu kacang kedelai terhadap karakteristik fisik, kimia dan mikrobiologi yoghurt - Hariyanto IH; Albianus Febri Tarung; Siti Nani Nurbaeti (Universitas Mataram, 2023)
The quality of yogurt is affected by the addition of durian fruit puree in milk. The aim of this study is to investigate how different concentrations of soy milk affect the physical, chemical, and microbiological properties of yogurt in comparison to the Indonesian National Standard (SNI). This research was conducted by making durian-flavored yogurt with variations of soy milk at concentrations of 8% (F1), 20% (F2), and 25% (F3). Yogurt was analyzed for organoleptic, pH, viscosity, syneresis, lactic acid content, protein content, and the number of lactic acid bacteria (LAB). The data was processed using SPSS one-way ANOVA statistics. The results showed that only the pH value did not meet the requirements of SNI for yogurt, with a range of 3.80-4.50 for all group concentrations. The viscosity numbers of F1, F2, F3, and control were 634.66, 614.66, 608, and 760.66 cp, respectively. F3 has shown the best stability in form based on syneresis results with a value of 91.93% compared to other groups, such as 90.69%, 91.65%, and 89.59% for F1, F2, and control, respectively. Lactic acid and protein compounds of all groups fulfill the SNI standard with a range of 1.7-1.83% and 3,03-3.23%, respectively. Similar results were shown in the LAB standard as well, showing the LAB numbers were >107 colonies/gram for all formulas. Soymilk addition increases the protein matrix stability determined in syneresis percentage.